Peningkatan Keterampilan Teknologi Informasi pada Pelaku Usaha di Desa Pasirtanjung, Kecamatan Tanjungsari, Kabupaten Bogor, Jawa Barat - Deasyanti; Erik; Suryaratri, Ratna Dyah; Megawati, Hermeilia (Universitas Negeri Jakarta, 2023)
The purpose of community service in Pasirtanjung Village, Tanjungsari District, Bogor Regency, West Java, is to improve the skills of UMKM in information technology to be able to compete in the current era of technological and information development. The implementation of the activity was carried out at the Village Head's Office which was attended by as many as 40 entrepreneur. This method of community service is carried out directly through the provision of skills training materials and access to capital. The results of this community service are quite good, as can be seen from the enthusiasm of UMKM in following the process of providing material. This activity is expected to be able to provide skills to UMKM so that they are able to compete in the era of increasingly rapid development of information technology. Keywords Desa Pasirtanjung, Teknologi Informasi, pelaku UMKM